ANALYSIS OF FACTORS AFFECTING THE DEMAND FOR MONEY IN INDONESIA - Fatihah, Vahlefi Rahmat; Pasaribu, Esti (LPPM STIE Muhammadiah Bandung, 2024)
Demand for money is defined as people's tendency to save money for various purposes, such as transactions, anticipation, and speculation. Many factors related to economic, social, political and psychological conditions influence the demand for money. This research aims to evaluate the impact of various variables on money demand in Indonesia from 2018 to 2023. This research uses an Error Correction Model (ECM), which can measure short-term and long-term correlations between the variables studied. The money supply (M2) is the dependent variable of this research, and the independent variables are interest rates, inflation and the US dollar exchange rate against the rupiah. The results show that except for inflation, all independent variables influence money demand significantly in the long run. In the short term, only the rupiah exchange rate has a significant influence on the demand for money.